Nanoparticle Direct Doping: Novel Method for Manufacturing Three‐Dimensional Bulk Plasmonic Nanocomposites. (15th February 2013) - Gajc, Marcin; Surma, Hancza B.; Klos, Andrzej; Sadecka, Katarzyna; Orlinski, Krzysztof; Nikolaenko, Andrey E.; Zdunek, Krzysztof; Pawlak, Dorota A.
Abstract Metallodielectric materials with plasmonic resonances at optical and infrared wavelengths are attracting increasing interest, due to their potential novel applications in the fields of photonics, plasmonics and photovoltaics. However, simple and fast fabrication methods for three‐dimensional bulk plasmonic nanocomposites that offer control over the size, shape and chemical composition of the plasmonic elements have been missing. Here, such a manufacturing method and examples of experimental realizations of volumetric isotropic nanocomposites doped with plasmonic nanoparticles that exhibit resonances at visible and infrared wavelengths are presented. This method is based on doping a low‐melting dielectric material with plasmonic nanoparticles, using a directional glass‐solidification process. Transmission‐spectroscopy experiments confirm a homogenous distribution of the nanoparticles, isotropy of the material and resonant behavior. The phenomenon of localized surface plasmon resonance is also observed visually. This approach may enable rapid and cost‐efficient manufacturing of bulk nanoplasmonic composites with single or multiple resonances at various wavelength ranges. These composites could be isotropic or anisotropic, and potentially co‐doped with other chemical agents, in order to enhance different optical processes.